Circle Passing Through Three points





In this page circle passing through three points we are going to see example problems to find the equation of a circle if three points passing through the circle is given.

Example 1:

Find the equation of a circle passing through the points (0,1) (2,3) and (-2,5).

The general equation of a circle

x² + y² + 2gx + 2fy + c = 0


Now we have to apply these points one by one in the above equation circle passing through three points

equation of a circle which is passing through the point (0,1)

                        0² + 1² + 2g(0) + 2 f(1) + c = 0

                               1 + 0 + 2f + c = 0

                                       2f  + c = -1  ----------(1)

equation of a circle which is passing through the point (2,3)

                        2² + 3² + 2g(2) + 2 f(3) + c = 0

                         4 + 9 + 4g + 6f + c = 0

                                  4g + 6f  + c = -13 ----------(2)

equation of a circle which is passing through the point (-2,5)

                   (-2)² + 5² + 2g(-2) + 2 f(5) + c = 0

                         4 + 25 - 4g + 10f + c = 0

                              -4g + 10f  + c = -29 ----------(3)

So the three equations are

                                       2f  + c = -1  ----------(1)

                                  4g + 6f  + c = -13 ----------(2)

                              -4g + 10f  + c = -29 ----------(3)

by solving these three equations we can get the values of f,g and c

by adding (2) and (3)

                                  4g + 6f  + c = -13 ----------(2)

                              -4g + 10f  + c = -29 ----------(3)

                             ----------------------

                                     16f + 2c = -42   ---------(5)

Multiplying (1) by 2

                                    4f + 2c = -2  

Subtract (5) form this equation

                                     16f + 2c = -42

                                      4f + 2c  = -2

                                     (-)   (-)     (+)    

                                   ----------------

                                       12f  = -40

                                           f = -40/12   

                                           f = -10/3

Substitute f = -10/3 in the first equation

                                 2(-10/3) + c = -1

                                   -20/3 + c = -1

                                               c = -1 + 20/3

                                               c = 17/3

substitute c = 17/3 and f = -10/3 in the second equation

              4g + 6(-10/3) + 17/3 = -13

              4g - 20 + 17/3 = - 13

                  4g + (-60+17)/3 = -13

                     4g - 43/3 = -13

                             4g = -13 + 43/3

                             4g = (-39+43)/3

                              4g = 4/3

                                g = 4/(4x3)

                                g = 1/3

Substitute g = 1/3 c = 17/3 ad f = -10/3 in the general equation

                    x² + y² + 2gx + 2fy + c = 0

       x² + y² + 2(1/3)x + 2(-10/3)y + 17/3 = 0                    

       x² + y² + (2/3)x + (-20/3)y + 17/3 = 0     

       3x² + 3y² + 2x -20y + 17 = 0         

So the equation of a circle passing through three points  3x² + 3y² + 2x -20y + 17 = 0

        Following are the related topics related to circle passing through three points.

Related Topics

HTML Comment Box is loading comments...








Circle Passing Through Threepoints to Analytical Geometry

Featured Categories 

Math Word Problems

SAT Math Worksheet

P-SAT Preparation

Math Calculators

Quantitative Aptitude

Transformations

Algebraic Identities

Trig. Identities

SOHCAHTOA

Multiplication Tricks

PEMDAS Rule

Types of Angles

Aptitude Test